SISTEM TRAFIK NAVIGASI WEB MENGGUNAKAN METODE SEQUENTIAL PATTERN - Lestari, Uning (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2010)
Analysis performed on web server logs have traditionally been widely used to see the web visitor activities such as determining the amount of access to web pages, anyone accessing the web user and the time to visit the web and visited URLs and more statistical analysis. But it is still very little information about the relationship between exis-ting data on the web, the sequence of requests made by a user or group of users who have access to a web site. To overcome these problems required a web mining tech-niques. Web mining is a technique to automatically discover and extract information on the web. This study used different techniques to sequential pattern Apriori algorithm to identify patterns of web site navigation. The the applications that have been made will show recapitulation of information about the number of visits per day, a search of browser used, details of visits that include IP addresses, proxy server, the location of the sequen-ce pattern visitor and web traffic. Web navigation patterns using Apriori is able to produce the sequence pattern of answering pages accessed by visitors. This pattern always varies depending on the minimum support are included. The higher MinSup, so little sequence variation pattern of visits and reverse the lower the value of the Minsup more and more variations of the sequence pattern of visits by users.